Novos algoritmos para controle de admissão de chamadas para o serviço de voz sobre IP em redes locais sem fio infra-estruturadas - Pimentel, Júlio Fernandes (2006)
In the last years, the IEEE 802.11 WLAN has become very popular and widely deploved for Internet acess. On the other hand, voice over IP is one of the fast growing Internet apllications today. Thanks to the convergence of these two trends, it is believed that VoIP over WLAN is expected to become an important Internet application. However, the so called "avalanche effect" has been identified as a real problem in a WLAN, when operating near its capacity limit, in which the admission of an additional call may result in unacceptable QoS for alll the ongoing VoIP connections. In this context, the call admission control has beeen pointed out as an interesting research issue. We have proceed the performance evaluation of four CAC algorithms. Two of them were fond in specialized literature, one based on a theoretical equation (EQA) and the other based on the channel busyness ratio (CBA). The other algorithms represent the innovative proposals of this work, one based on the measured downlink FER (FEA) and the other based on the transmission buffer utilization ratio (BSA). The resource allocation provided by the FEA is more efficient than the one provided by EQA or CBA. However, this algorithm considers the accurate availability of the downlink FER metric at the access point. The BSA has almost eliminated the "avalache effect" achieving the best gains in terms of capacity and resource allocation when comparing with all the algorithms evaluated. Additionally, the practical implementation of the BSA is very simple and the decision metric is readily available at the access point